2006
DOI: 10.1177/0092070305283356
|View full text |Cite
|
Sign up to set email alerts
|

Brands Matter: An Empirical Demonstration of the Creation of Shareholder Value Through Branding

Abstract: This research responds to the attendant need for empirical evidence pertaining to how marketing affects firm performance. Using the Fama-French method, common in finance, and a leading marketplace measure of a brand’s financial equity value, the authors provide empirical evidence for the branding-shareholder value creation link. The results extend previous research by showing that strong brands not only deliver greater returns to stockholders than does a relevant benchmark but do so with less risk. This findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
291
1
21

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 409 publications
(352 citation statements)
references
References 19 publications
16
291
1
21
Order By: Relevance
“…Results showed that companies with higher focus on the brand values performed exceptionally well and have fetched better results in respect of the monthly returns than the lesser brand concerned organizations. The results of the research also showed that a considerable amount of shareholders value creation was possible as reflected through the regression analysis (Madden et al, 2006).…”
Section: Brand Equity and Success In Businessmentioning
confidence: 74%
See 2 more Smart Citations
“…Results showed that companies with higher focus on the brand values performed exceptionally well and have fetched better results in respect of the monthly returns than the lesser brand concerned organizations. The results of the research also showed that a considerable amount of shareholders value creation was possible as reflected through the regression analysis (Madden et al, 2006).…”
Section: Brand Equity and Success In Businessmentioning
confidence: 74%
“…In order to create a long lasting effect of the brand among the prospects and the customers, organizations have used various marketing techniques. Among the marketing techniques used, advertising has been one of the most popular methods (Wang et al, 2009;Madden et al, 2006). However it is noted that the initial effect of the advertising of the brand values disseminates within a period of three to fifteen months.…”
Section: Brand Equity and Success In Businessmentioning
confidence: 99%
See 1 more Smart Citation
“…The Interbrand measure addresses criticisms concerning the lack of objectivity in BE measures based exclusively on customer mind-set, such as the one Millward Brown uses (Ailawadi et al, 2003). Madden et al (2006) defend the use of Interbrand data as the most well-known and widely used brand valuation method (Haigh and Perrier, 1997).…”
Section: Variablesmentioning
confidence: 99%
“…Study after study demonstrates that strong brands create higher amounts of shareholder value, by increasing revenue and margin growth and decreasing the riskiness of a company ' s cash fl ows, more effectively than weak brands (see Millward Brown, 1 Interbrand 2 and Madden et al 3 ). According to some authors of popular management books, building such brands requires the application of simple ' laws ' of branding (see, eg Alsop 4 and Ries and Ries 5 ).…”
Section: Introductionmentioning
confidence: 99%